2011
DOI: 10.1002/ajhb.21143
|View full text |Cite
|
Sign up to set email alerts
|

Bioimpedance analysis: Should it be used in morbid obesity?

Abstract: BIA limitations were mostly relevant for males, not females. Despite such discrepancies, good associations with anthropometry were demonstrated for both genders. Correlations with liver enzymes, and indices of protein, carbohydrate, and lipid metabolism could be demonstrated. BIA deserves more investigations concerning liver steatosis and ongoing inflammation, and it could contribute as well, synergistically with anthropometry, to monitor weight loss, body fat shifts, and metabolic risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 12 publications
2
11
0
4
Order By: Relevance
“…The present multidisciplinary intervention led to a significant reduction of fat mass of obese individuals with binge eating similar to the data presented by Savastano et al & Leal et al [33,34]. Both reports have shown that weight loss and reduction of binge eating have a positive effect on reducing fat mass and consequently reducing cardiovascular risk.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…The present multidisciplinary intervention led to a significant reduction of fat mass of obese individuals with binge eating similar to the data presented by Savastano et al & Leal et al [33,34]. Both reports have shown that weight loss and reduction of binge eating have a positive effect on reducing fat mass and consequently reducing cardiovascular risk.…”
Section: Resultssupporting
confidence: 74%
“…This reduction may be reflecting a greater amount of free water in this group and therefore, parallel to the reduction of weight, a significant reduction of the amount of free water could have occurred, not necessarily reflecting sarcopenia [34].…”
Section: Resultsmentioning
confidence: 99%
“…We were aware that BIA in severely obese patients has been criticized because these patients may have altered electrical properties in their body tissues, which could cause an overestimation of FFM and an underestimation of FM [19,20]. In addition, as reported in a recent review of Mialich et al [21], standardization of measurement conditions is essential for obtaining accurate, precise, and reproducible BIA.…”
Section: Discussionmentioning
confidence: 97%
“…Podobně je požadováno další ověření validity BIA např. ve stavech akutního onemocnění (Faisy et al, 2000), extrémních hodnotách tělesné hmotnosti (Deurenberg et al, 1996, Vansant et al, 1994, Leal et al, 2011 a při neobvyklém abnormálním tvaru těla (Driskel et al, 2011).…”
Section: úVodunclassified